On the use of sentiment analysis for linguistics research. Observations on sentiment polarity and the use of the progressive in Italian - Viola, Lorella (Frontiers in Artificial Intelligence, 2023)
This article offers a conceptual and methodological contribution to linguistics by exploring the potential value of using sentiment analysis (SA) for research in this field. It discusses the limitations and advantages of using SA for linguistics research as well as the wider epistemological implications of its application outside of its original conception as a product reviews analysis tool. Methodologically, it tests its applicability against an established linguistic case: the correlation between subjective attitudes such as surprise, irritation and discontent and the use of the progressive. The language example is Italian for which this function of the progressive form has not been analysed yet. The analysis applies FEEL-IT (Bianchi, Nozza, and Hovy 2021), a state-of-the-art transformer-based machine learning model for emotion and sentiment classification in Italian on language samples from various sources as collected in Evalita-2014 (Bosco et al. 2014) (238,556 words). The results show statistically significant correlations between negative subjective attitudes and the use of the progressive in line with previous accounts in other languages. The article concludes with a few additional propositions for practitioners and researchers using SA.